SARS‐CoV‐2: the prospects of the virus spreading and the course of the pathogenesis of coronavirus infection in various species of animals - M. S. Fedotova; A. Yu. Filippova; M. A. Omarov; K. S. Yurchenko; M. A. Gulyaeva (Юг России: экология, развитие, 2022)
Aim. Analyse available literature data about the possibility of coronavirus infection with and the severity of the course of infection in various animal species in order to evaluate the significance of this possibility in the context of preservation of the well‐being of both wild and domestic animals.Discussion. SARS‐CoV‐2 is thought to have originated from bat CoV. The virus enters the cell by binding to the ACE2 receptor, the affinity for which differs depending on the animal species. Infected animals show viral RNA and may show clinical symptoms. It is known that the virus originated from some animals, while others may be carriers. Moreover, it can be that wild as well as domestic and farm animals are in close contact with humans. Therefore, it is advisable to conduct a study of the degree of threat to humans associated with the persistence of the virus in animal communities.Conclusion. There is ample literature on the possibility of infection in various animals. However, it is not enough to fully understand how significant is the role that animals can play in the spread of coronavirus infection among humans and how much harm it can bring to themselves.